2021
DOI: 10.1002/ejic.202100101
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Mixed‐Valence Luminescent Silver Clusters via Cation‐Coupled Electron‐Transfer in a Redox‐Active Ionic Crystal Based on a Dawson‐type Polyoxometalate with Closed Pores

Abstract: A redox‐active ionic crystal based on a Dawson‐type polyoxometalate (POM) [α‐P2WVI18O62]6− is utilized to form and stabilize small mixed‐valence luminescent silver clusters without the aid of protecting ligands at room temperature. A reduced ionic crystal of Cs3H5[Cr3O(OOCH)6(etpy)3]3[α‐P2WV5WVI13O62] ⋅ 5H2O (etpy=4‐ethylpyridine) is formed by a cation‐coupled electron‐transfer (CCET) reaction with sodium ascorbate as a reducing reagent to provide electrons and Cs+ as counter cations of POM. Then, silver is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 36 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…According to the observation above, we reached the idea that smaller Ag clusters can be synthesized by regulating the electron transfer from the PIC to Ag + . Therefore, we focused on [a‐P 2 W VI 18 O 62 ] 6– because [a‐P 2 W VI 18 O 62 ] 6– stores fewer electrons than [a‐P 2 Mo VI 18 O 62 ] 6– under the same reducing conditions, [ 43,53 ] and utilized K 3 [Cr 3 O(OOCH) 6 (etpy) 3 ] 3 [a‐P 2 W VI 18 O 62 ]· n H 2 O [ 45 ] [ K‐I W (0, 0) ] as a scaffold to synthesize Ag clusters. The PXRD patterns showed that K‐I Mo (0, 0) and K‐I W (0, 0) were isostructural (Figure S8, Supporting Information), and the abbreviation K‐I W ( t 1 , t 2 ) is defined in the same way as K‐I Mo ( t 1 , t 2 ) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the observation above, we reached the idea that smaller Ag clusters can be synthesized by regulating the electron transfer from the PIC to Ag + . Therefore, we focused on [a‐P 2 W VI 18 O 62 ] 6– because [a‐P 2 W VI 18 O 62 ] 6– stores fewer electrons than [a‐P 2 Mo VI 18 O 62 ] 6– under the same reducing conditions, [ 43,53 ] and utilized K 3 [Cr 3 O(OOCH) 6 (etpy) 3 ] 3 [a‐P 2 W VI 18 O 62 ]· n H 2 O [ 45 ] [ K‐I W (0, 0) ] as a scaffold to synthesize Ag clusters. The PXRD patterns showed that K‐I Mo (0, 0) and K‐I W (0, 0) were isostructural (Figure S8, Supporting Information), and the abbreviation K‐I W ( t 1 , t 2 ) is defined in the same way as K‐I Mo ( t 1 , t 2 ) .…”
Section: Resultsmentioning
confidence: 99%
“…550 nm) color, respectively (Figure 5b,e). The Ag clusters formed in K‐I W (60, 60) can be assigned mainly to [Ag 4 ] 2+ according to the position of the maximum in the PL spectrum, [ 45 ] which is largely blue‐shifted from that of K‐I Mo (60, 60) (maximum at ca. 715 nm) containing [Ag 6 ] 2+ , consistent with our expectation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 30,36,64,65 ] Indeed, this is the case for Ag31+Ni22+Bi5+O62$\rm Ag_3^{1+}Ni_2^{2+}Bi^{5+}O_6^{2-}$, whereby the Ag$\rm Ag$ atom is monovalent, and the lattice is not only monolayered but triangular, [ 38 ] in contrast to the present material reported herein. Meanwhile, the Ag$\rm Ag$ sub‐valent state 1/3+$1/3+$ remains conspicuously absent in reported layered materials [ 30,36,64 ] and other silver‐rich oxides, [ 41–43,71–77 ] despite its presence reported, e.g., in Ag31/3+O2H1+$\rm Ag_3^{1/3+}O^{2-}H^{1+}$. [ 78 ] Finally, although the sub‐valency of silver remains unascertained in the present material via direct XPS measurements of Ag$\rm Ag$ binding energies, the fact that the Ag$\rm Ag$‐rich domains are bilayered with an apparent bifurcated bipartite honeycomb lattice demonstrates that such domains fit well within the aforementioned class of bilayered sub‐valent Ag$\rm Ag$‐based frameworks, thus corroborating the charge neutrality argument provided earlier for the sub‐valency of Ag$\rm Ag$.…”
Section: Discussionmentioning
confidence: 99%